Co-evolution of tourism and industrial sectors: the case of the Bełchatów industrial district - Napierała, Tomasz; Leśniewska-Napierała, Katarzyna; Nalej, Marta; Pielesiak, Iwona (European Spatial Research and Policy, 2024)
The goal of the study is to explore the co-evolution of the tourism and industrial sectors. This paper addresses the concept of inter-path dependency as the theoretical framework for this study. The case study of Bełchatów industrial district is applied to discuss the co-evolution of tourism and heavy industries. Tourism and heavy industries are usually seen as mutually exclusive. However, in the case of the Bełchatów industrial district, tourism (starting from social tourism, through business tourism and educational tourism) is confirmed as being complementary to the industrial path shaped by triggering events (launch of radical industrialisation, and economic transition). Recently, implementation of the Just Transition Mechanism was planned and includes development of leisure tourism in the case study area. Some doubts of that intersectoral linkages are discussed in the paper – mainly in the context of the expected sustainable development of the Bełchatów industrial district – and followed by policy recommendations.